Systems Reliability, Footprints and Sustainability - Akos Orosz; Ferenc Friedler; Petar S Varbanov; Jiri Jaromir Klemes (Chemical Engineering Transactions, 2018)
Systems reliability and availability are critical aspects that should be tackled simultaneously within process design, alongside the widely considered profit and environmental impacts affecting sustainability. In optimal process synthesis, the combination of process design with other aspects can be modeled by adding constraints to the problem formulation or by additional terms in the objective function. Independently of the formulation, the reliability and sustainability aspects have an adverse effect on the profitability of the process. Providing for sustainability in process design usually reduces the profit by increasing the cost. Reliability is considered in process design for improving the availability of the system. In this way, it acts in synergy with the other process factors to improve the profitability of the process. Improving process reliability, in addition to raising availability and direct profits, can also contribute significantly to reducing the risk of catastrophes, negative environmental impact and human injury. This contributes to the environmental and societal components of sustainability. Despite this potential advantage, the simultaneous optimization of reliability and sustainability improvement has not been considered. This work introduces a new method to consider reliability and sustainability in process design as an important extension of the basic process design. The result is illustrated by the design of a process considering profitability, sustainability and reliability simultaneously.